2008
DOI: 10.1590/s1415-54192008000300005
|View full text |Cite
|
Sign up to set email alerts
|

Colagem ortodôntica em esmalte com presença ou ausência de contaminação salivar: é necessário o uso de adesivo auto-condicionante ou de adesivo hidrofílico?

Abstract: OBJETIVO: o objetivo deste trabalho foi avaliar a resistência ao cisalhamento da colagem ortodôntica de um adesivo hidrofílico (Transbond Moisture-Insensitive Primer, 3M Unitek, Monrovia, Califórnia), de um adesivo auto-condicionante (Transbond Self-Etching Primer, 3M Unitek, Monrovia, Califórnia), e sem uso de adesivo, em superfícies de esmalte secas ou contaminadas por saliva. METODOLOGIA: incisivos bovinos (60) foram divididos em 6 grupos: (1) controle sem contaminação salivar (sem adesivo), (2) controle co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 18 publications
(29 reference statements)
1
9
0
Order By: Relevance
“…As in other studies, all tests in the present study were higher than the average proposed. 13,20,23 When comparing the resins, the statistical difference result between groups stands out. The analysis reveals that the G4 appeared more resistant to shear than G3.…”
Section: Discussionmentioning
confidence: 98%
“…As in other studies, all tests in the present study were higher than the average proposed. 13,20,23 When comparing the resins, the statistical difference result between groups stands out. The analysis reveals that the G4 appeared more resistant to shear than G3.…”
Section: Discussionmentioning
confidence: 98%
“…3,4,11,17 The substrate used in our study was bovine tooth enamel, as in other studies. 4,5,13,16 Bovine teeth are anatomically, histologically and chemically similar to human teeth, although bond strength result shows to be lower than those of human teeth. 8,9 In this study, the samples used for the bond strength trial were cylinders made of Transbond™ XT composite resin.…”
Section: E5mentioning
confidence: 98%
“…Other studies found higher bond strength results for Transbond™ MIP in dry environments, 3 and some authors believed that they were higher than recommended for orthodontic bracket bonding. 13 Therefore, not only bond strength, but also bonding characteristics, such as mechanisms and depth of penetration of different adhesives in the tags formed during enamel etching, are factors that should be evaluated and taken into consideration when making a decision about which materials to use.…”
Section: E5mentioning
confidence: 99%
See 1 more Smart Citation
“…According to the authors, these results may be related to (a) difficulty in maintaining proper isolation of the region, (b) inadequate adaptation of the attachment base to the tooth surface, (c) stronger masticatory forces, (d) different etching times, and (e) individual variations related to enamel composition. 8 Nowadays, however, given recent advances in primer quality 4,16,17 and in the bases of orthodontic attachments 11 manufactured for direct bonding, combined with awareness of the benefits of this procedure, it would be convenient to devise methods capable of increasing the efficiency of traditional bonding, notably in teeth subjected to higher masticatory impact, such as lower molars. In reviewing the literature, only one study was found which evaluated in vitro an alternative approach to reduce the percentage of failures in the direct bonding of molars.…”
Section: Introductionmentioning
confidence: 99%